Prognostic Value of Immunoscore and PD-L1 Expression in Metastatic Colorectal Cancer Patients with Different RAS Status after Palliative Operation. (31st January 2018) - Liu, Ruiqi; Peng, Ke; Yu, Yiyi; Liang, Li; Xu, Xiaojing; Li, Wei; Yu, Shan; Liu, Tianshu
Abstract : Colorectal cancer (CRC) is the fifth leading cause of cancer death and the fifth most commonly diagnosed cancer in China. Approximately, 25% of CRC was in the advanced stage as diagnosed, and 40% of patients with CRC progress to metastatic colorectal cancer (mCRC). RAS mutation status is now routinely used to select their therapy. But it is still a question whether RAS mutation status is a prognostic marker. In our study, we detected RAS mutation, immunoscore (IS), and PD-L1 expression in 60 Chinese mCRC patients who received palliative operation. The Kaplan-Meier survival analysis showed that the overall survival (OS) in patients with RAS wild type was better than those with RAS mutated type. Moreover, in multivariate analysis, RAS mutation and PD-L1 expression were demonstrated to be the independent negative prognostic factors for OS (P = 0.044, HR: 0.258, and 95% CI: 0.069–0.967;P = 0.048, HR: 0.276, and 95% CI: 0.077–0, 988). All results suggested that, combined with IS, PD-L1 expression and RAS status may be the prognostic indicators for mCRC patients with palliative operation.